Research on Multi-Scenario Variable Parameter Energy Management Strategy of Rural Community Microgrid - Lidong Guo; Zilong Yang; Yibo Wang; Honghua Xu (Applied Sciences, 2020)
Many rural communities in western China use renewable energy-based clean energy supply methods, and the community microgrid system of “photovoltaic + energy storage + electric heating” has been widely used. However, the energy management effect of such a typical rural community microgrid system is not very satisfactory. Aiming at the problem of the comprehensive economic operation of the microgrid system in rural communities, a method for optimizing the operation strategy parameters of typical operating scenarios is proposed, and critical parameters of the real-time energy management strategy of the microgrid system are optimized. Through the evaluation of the annual time-scale simulation results, it is proved that the proposed strategy can improve the comprehensive economic benefits of the operation of the rural community microgrid system (comprehensive economic benefits include electricity bills and energy storage system (ESS) life loss). Relying on the actual community microgrid demonstration project system in western China, a community-level microgrid energy management monitoring system is built. The control strategy proposed in this paper is applied to the demonstration system for experimental verification. The operational data of the demonstration system shows that the proposed method is feasible and effective.